(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Conflict is a normal and usual part of the workplace. It happens in every business. For any team that wants to accomplish its goals, conflict is inevitable. While differences will occur, the effect doesn’t have to be negative. Conflict can produce openings. Conflict challenges us to think harder, to be more creative, to achieve greater understanding, and to search for alternative approaches that are more effective, more sustainable, and more successful. Unresolved conflict, however, can result in the dissolution of a group. When unaddressed tension occurs in the workplace, it can decrease productivity, hamper production, and increase absenteeism. It leads to increased stress among staff, decreased morale, and at worst, aggression or violence. Studies recommend that managers spend at least 25 percent of their time handling internal conflicts. This affects the productivity of the work force and can have a dramatic impact on organizational performance. Real-life situations, especially in the realms of competition and partnership, games will reveal the conventional way conflict is dealt with in the squad. Teams can begin to appreciate their usual solutions, and then go on to find more effective methods for dealing with similar scenarios. Experiential exercises allow team members to learn their reactions to conflict and their subsequent actions. In this journal, the observational analysis with regard to future workplace conflicts, we try to explore the means and the skills to bring about positive results by playing in conflict-resolution games, improve teamwork and challenge inefficient processes to create a team that is more unified and more successful.